Method development to characterise elephant tail hairs by LA-ICP-MS to reflect changes in elemental chemistry - Fiona Sach; Lorraine Fields; Simon Chenery; Lisa Yon; Michelle D. Henley; Peter Buss; Ellen S. Dierenfeld; Simon C. Langley-Evans; Michael J. Watts (Environmental Geochemistry and Health, 2023)
This paper evaluated analytical methods used to generate time-series data from elephant tail hairs, which can be used to reflect changing exposure to environmental geochemistry. Elephant tail hairs were analysed by three methods sequentially, each providing data to inform subsequent analysis. Scanning Electron Microscopy (SEM) and X-ray Microanalysis visually showed the structure of the hair, specific structures such as tubules, and the mineral crusting around the edge of the hair, informing targeting of subsequent analysis by Laser Ablation-Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS). LA-ICP-MS generated time-series data which informed sectioning of the tail hairs for subsequent quantitative analysis for potentially toxic elements and micronutrients using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) of dissolved tail hairs. This novel approach to characterise the tail hair enabled time-series analysis to reflect changes in environmental exposure which may result from seasonal or geochemical spatial variation and could inform elephant movement patterns. The seasonal change between wet and dry seasons was reflected down the length of the hair. Correlations were seen between LA-ICP-MS data and ICP-MS data in several elements including Mg, P, Ca, Fe, Na, Mn and U. This study provided time-series data for the analysis of elephant tail hairs by evaluating analytical challenges to obtaining quantitative data, such as improving protocols to ensure removal of extraneous material, determining where to section the tail hairs to best reflect environmental changes/exposure and ensuring representative analyses. A protocol was established to determine mineral status across a 12–18 month time period utilizing single elephant tail hairs.